Anti-arrhythmic effects of morlincain - Zhang Yan-Li; Rui Yao-Cheng; Tu Shi-Zhong (Acta Pharmacologica Sinica, 2016)
The anti-arrhythmic effects of morlincain (Mor, 2-morpholino-2’,6’-dimethyl acetanilide), a lidocaine analog synthesized firstly in 1984 in China, were studied. The values of ED50 of ip Mor against ventricular tachycardia (VT) or ventricular fibrillation (VF) induced by chloroform, and the cardiac arrest induced by iv aconitin in mice were 129 (95% fiducial limits 100-159) and 115 (98-135) mg/kg, respectively. Pretreatment of guinea pigs with iv Mor (80 mg/kg) increased the doses of ouabain causing ventricular premature beats (VP), VT, VF and cardiac arrest by 50, 55, 43 and 44%, respectively. VP numbers and VT duration induced by coronary artery ligation in rats were reduced by iv Mor 100 mg/kg followed by infusion of 50 mg/(kg·h). Mor was ineffective against BaCl2-induced arrhythmia in rats. Mor was found to have a weak local anesthetic activity. 20% and 10% Mor inhibited rabbit corneal reflex and skin reflex of guinea pigs, respectively. Mor 142 mg decreased MBP and cardiac output in anesthetized open-chest cats and the minimal lethal dose was 1241±94 mg/kg. Its LD50 was 748 (667-844) mg/kg in mice by ip.